Determinação da priorização de equipamentos para manutenção por método de criticidade - estudo de caso - Castro Neto, Onias Pereira de (2017)
This work includes several aspects related to the Maintenance function. The study aims at the application of a method for the prioritization of the equipment for the Maintenance of a process of Generation of Energy and Steam. In order to identify the criticality of the equipment, a pilot system was defined for the study and application, standardization and accomplishment of the equipment installation locations, adjustment of the criteria parameters according to the specific application and elaboration of a tool for data collection and analysis. definition of criticality based on the proposed method. The tool also aims to indicate maintenance techniques considered essential for each equipment analyzed. Throughout the development of the work, several complementary activities were necessary and included in the methodology, such as the survey of the technical and operational data of these equipaments for the structuring of the hierarchy of the processes. Among the justifications of the work, we highlight the optimization of the company's maintenance resources, the increase of equipment usefulness, base contribution to integrated maintenance management, increased availability and reliability of the process through the use of appropriate methods of maintenance management. The results obtained were considered positive, since the critical equipment of the analyzed set was identified through the elaborated tool, so that the standardized procedure can be applied to all facilities of the unit.